Preparation method and application of organic / inorganic composite flocculant for swimming pool water treatment

By preparing Fe3O4-PSAZn-CS-AM composite flocculant, the potential risks of existing swimming pool water treatment methods to human health and the difficulty in removing complex organic components and heavy metal ions are solved, achieving efficient and safe water treatment effect.

CN119551778APending Publication Date: 2025-03-04PUYANG CLEANWAY CHEM +1

Patent Information

Application Number
CN202311124066.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing pool water treatment methods have potential risks to human health and are difficult to effectively remove complex organic components and heavy metal ions.

Method used

Using an organic/inorganic composite flocculant, a magnetic polysilicic acid solution is prepared by mixing magnetic nanoparticle Fe3O4 with sodium silicate powder and crosslinking with chitosan-polyacrylamide flocculant to prepare Fe3O4-PSAZn-CS-AM composite flocculant. This flocculant can not only adsorb organic matter, but also absorb heavy metal ions.

Benefits of technology

It realizes efficient removal of organic matter and heavy metal ions in the swimming pool water, and due to the magnetic properties of the flocculant, it is easy to separate and recover, reduces treatment costs, and has no toxic side effects on the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551778A_ABST
    Figure CN119551778A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and particularly relates to a preparation method and application of an organic / inorganic composite flocculant for swimming pool water treatment.The method comprises the steps that magnetic nanoparticles Fe3O4 and sodium silicate powder are mixed to prepare a magnetic polysilicic acid solution, chitosan and acrylamide of a certain mass are dissolved in a glacial acetic acid solution, and the magnetic polysilicic acid solution is prepared; and ammonium ceric nitrate is used as an initiator to prepare the chitosan-polyacrylamide flocculant. The prepared chitosan-polyacrylamide flocculant is stirred in a glacial acetic acid solution for 24 hours for pretreatment. The preparation method comprises the following steps: adding an Al2 (SO4) 3.18 H2O solution, a ZnSO4. 7H2O solution and a pretreated chitosan-polyacrylamide flocculating agent into a magnetic polysilicic acid solution according to a certain proportion, so as to prepare the Fe3O4-PSAZ-CS-AM composite flocculating agent. The method disclosed by the invention is simple in reaction operation, easy in reaction condition control, low in cost and high in turbidity removal and organic matter removal efficiency of the swimming pool water, and has relatively high popularization and application values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a preparation method and application of an organic / inorganic composite flocculant for swimming pool water treatment. Background Art

[0002] In recent years, with economic development and a growing emphasis on health, swimming has become a highly popular sport, raising the bar for pool environments and water quality. Compared to tap water, pool water contains a complex composition of organic matter, including not only organic matter from the water but also various organic secretions, metabolites, and personal care products carried by the human body. Using a single treatment method can be ineffective. Current methods for pool water disinfection primarily use chlorine-containing disinfectants, which have drawbacks, such as their tendency to react with organic matter to form byproducts such as chloroform and chloroacetic acid, which pose risks to human health.

[0003] Flocculation, one of the most commonly used water treatment methods, offers advantages such as high efficiency, low energy consumption, simple operation, and environmental friendliness. Chitosan is a natural high-molecular-weight organic flocculant derived from animal shells. It is widely available, inexpensive, and readily biodegradable, with a molecular weight of 120,000 to 590,000 and excellent adsorption and bridging capabilities. Furthermore, the presence of numerous free hydroxyl and amino groups on chitosan molecular chains makes it highly reactive, allowing it to undergo chain substitution and chain extension reactions with other adsorbent polymers. The numerous active groups and long-chain molecular structure of polyacrylamide facilitate complex adsorption of metals and metal oxides, resulting in the formation of flocculated particles that settle. Cross-linking with chitosan further enhances the flocculation effect. Fe₃O₄ magnetic nanoparticles are a rapidly developing and highly valuable new material in recent years. They exhibit excellent biocompatibility, high biosafety, and low toxicity. They also exhibit nanoscale size effects, high surface area, high surface activity, and ease of modification with functional groups. Their superparamagnetic properties make magnetic composite flocculants easier to separate and recover, leading to increasing interest in water treatment. Magnetic Fe₃O₄ composite materials can also be recycled and reused under the influence of a magnetic field, saving processing costs and making them environmentally friendly water treatment flocculants. To safely and efficiently treat swimming pool water and protect human health, it is essential to develop a composite flocculant that can adsorb both organic matter and heavy metal ions. Summary of the Invention

[0004] The purpose of the present invention is to provide a preparation method and application of an organic / inorganic composite flocculant for swimming pool water treatment, which has no toxic side effects on the human body, is simple to prepare, and is low in cost. Compared with traditional single organic flocculants, inorganic flocculants or simply physically mixed organic / inorganic flocculants, the present invention has better flocculation effect, a wider range of use, and high promotion and use value.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing an organic / inorganic composite flocculant for swimming pool water treatment comprises the following steps: S1. Preparation of magnetic nanoparticles: FeCl3·6H2O and FeCl2·4H2O were dissolved in 150 mL of 4% hydrochloric acid solution, iron powder was added to the FeCl2·4H2O solution and then mixed with the FeCl3·6H2O hydrochloric acid solution. While mixing, 25% ammonia water was added and stirred for 2 h. The mixture was allowed to stand and washed three times with deionized water and anhydrous ethanol respectively to obtain Fe3O4 magnetic nanoparticles with a particle size distribution of 8 to 20 nm. The particles were dried and ground at 50 °C for later use. The prepared Fe3O4 magnetic nanoparticle powder was dissolved in 50 mL of deionized water to prepare a concentration of 1.45 g·L -1 Fe3O4 magnetic nanoparticle solution; S2. Preparation of magnetic sodium silicate solution: at a concentration of 1.45 g·L -1 Sodium silicate powder was added to the Fe3O4 magnetic nanoparticle solution and 30% concentrated sulfuric acid and 0.1 mol·L -1 The pH value of the mixed solution was adjusted to 1.0 with sodium hydroxide, stirred in a 40℃ water bath for 2 h, and allowed to stand for 2 h to prepare a magnetic polysilicic acid solution. S3. Preparation of chitosan-polyacrylamide flocculant: Chitosan and acrylamide were dissolved in glacial acetic acid solution, and cerium ammonium nitrate was used as an initiator to prepare chitosan-polyacrylamide flocculant CS-AM. The prepared flocculant was stirred in glacial acetic acid solution for 24 hours for pretreatment. S4. Preparation of organic / inorganic composite flocculant: 0.427 mol·L-1 of CS-AM was added to the magnetic polysilicic acid solution according to the ratio of n(Al+Zn) / n(Si) = 0.8, n(Al) / n(Zn) = 4, and m(Al+Zn) / m(CS-AM) = 4. -1 Al2(SO4)3·18H2O solution, 0.854 mol·L -1 The ZnSO4·7H2O solution and 0.5% pretreated CS-AM solution were cross-linked and stirred in a 40℃ water bath for 2 h, and then left to stand and mature for 24 h to prepare Fe3O4-PSAZn-CS-AM composite flocculant.

[0006] Furthermore, the composite flocculant is post-treated before use, and the post-treatment includes first purifying it with acetone, then washing it with anhydrous ethanol until there is no impurity, and then drying it in a constant temperature drying oven to a constant weight.

[0007] The invention discloses a method for preparing an organic / inorganic composite flocculant for swimming pool water treatment. The composite flocculant is used in swimming pool water treatment to adsorb heavy metal ions while adsorbing organic matter.

[0008] The present invention has the following advantages: magnetic nanoparticles Fe3O4 are mixed with sodium silicate powder to prepare a magnetic polysilicic acid solution; a certain amount of chitosan and acrylamide are dissolved in a glacial acetic acid solution; and ammonium cerium nitrate is used as an initiator to prepare a chitosan-polyacrylamide flocculant. The prepared chitosan-polyacrylamide flocculant is stirred in the glacial acetic acid solution for 24 hours for pretreatment. Al2(SO4)3·18H2O solution, ZnSO4·7H2O solution, and the pretreated chitosan-polyacrylamide flocculant are added to the magnetic polysilicic acid solution in a certain proportion to prepare a Fe3O4-PSAZ-CS-AM composite flocculant. The present invention has simple reaction operation, easily controllable reaction conditions, low cost, high efficiency in removing turbidity and organic matter from swimming pool water, and high application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a scanning electron microscope image of Example 1 of the present invention; in the figure: a-chitosan-polyacrylamide flocculant (CS-AM), b-modified magnetic polysilicate aluminum zinc-chitosan-acrylamide composite flocculant (Fe3O4-PSAZn-CS-AM); Figure 2 1 is an XRD pattern of Example 1 of the present invention; in the figure: a-chitosan-polyacrylamide flocculant (CS-AM), b-modified magnetic polysilicate aluminum zinc-chitosan-acrylamide composite flocculant (Fe3O4-PSAZn-CS-AM); Figure 3 This is a scanning electron microscope image of Example 2 of the present invention after the reaction; Figure 4 2 is a schematic diagram of turbidity removal rate of Example 2 of the present invention; Figure 5 Schematic diagram of the organic matter removal effect of Example 3 of the present invention; Figure 6 The composite flocculant is used to measure the turbidity, COD concentration, urea concentration and UV of swimming pool water samples. 254 Schematic diagram of the removal effect. DETAILED DESCRIPTION

[0010] Example 1 A method for preparing an organic / inorganic composite flocculant for swimming pool water treatment comprises the following steps: Step 1: Dissolve 11.6 g of FeCl₃·6H₂O and 3.6 g of FeCl₂·4H₂O in 150 mL of 4% hydrochloric acid solution. Add a small amount of iron powder to the FeCl₂·4H₂O solution and rapidly mix the two solutions. Simultaneously, add 25% aqueous ammonia. Stir the mixture for 2 hours, allow it to stand, and then rinse it three times with deionized water and then with anhydrous ethanol. This yields Fe₃O₄ magnetic nanoparticles with a particle size distribution of 8 to 20 nm. Dry and grind the mixture at 50°C for later use.

[0011] Step 2: Take an appropriate amount of Fe3O4 nanoparticle powder and dissolve it in 50 mL of deionized water to prepare a concentration of 1.45 g·L -1 of Fe3O4 solution.

[0012] Step 3: Add 2.004 g of sodium silicate powder to the Fe3O4 solution and use 30% concentrated sulfuric acid and 0.1 mol·L -1 The pH value of the mixed solution was adjusted to 1.0 with sodium hydroxide, stirred in a 40°C water bath for 2 h, and allowed to stand for 2 h to obtain a magnetic polysilicic acid solution.

[0013] Step 4: Pretreat the CS-AM solution with 1% glacial acetic acid solution.

[0014] Step 5: Add 0.427 mol·L of CS-AM to the magnetic polysilicic acid solution according to the ratio of n(Al+Zn) / n(Si) = 0.8, n(Al) / n(Zn) = 4, and m(Al+Zn) / m(CS-AM) = 4. -1 Al2(SO4)3· 18H2O solution, 0.854 mol·L -1 The ZnSO4·7H2O solution and 0.5% pretreated CS-AM solution were stirred in a 40℃ water bath for 2 h and allowed to stand for 24 h to prepare the Fe3O4-PSAZn-CS-AM composite flocculant.

[0015] Performance and structure characterization Scanning electron microscopy was used to observe the surface characteristics of the samples. Figure 1 ,in Figure 1 (a) CS-AM polymer, unmodified with inorganic nanoparticles, has a lamellar structure with numerous wrinkles and protrusions. The polymer's rough surface and large specific surface area adsorb and capture suspended matter and impurities in the pool water, achieving flocculation. The addition of Fe₃O₄ magnetic nanoparticles results in a composite flocculant with a rougher surface and a more porous structure. This structure, with its increased voids, further enhances the flocculant's flocculation effectiveness.

[0016] In order to accurately analyze the crystal structure of the sample, X-ray diffraction was performed on the flocculant. Figure 2 (a) is the X-ray diffraction pattern of chitosan-polyacrylamide, which has only one strong diffraction peak at 2θ=20.6°. Figure 2 (b) is the X-ray diffraction pattern of Fe₃O₄-PSAZn-CS-AM. Diffraction peaks appear at 2θ values ​​of 30.2°, 35.5°, 43.2°, 57.1°, and 62.7°, which are consistent with those of a standard Fe₃O₄ card, indicating the presence of magnetic nanoparticles in the composite material and consistent with the diffraction peak positions of magnetic chitosan reported in the literature. The diffraction peak intensity at 2θ = 20.6° is significantly weakened, demonstrating that the addition of magnetic nanoparticles and metal ions alters the polymer structure, producing a new amorphous polymer. Therefore, this composite flocculant is not a simple mixture of several compounds, but rather a molecular interaction that significantly increases the rate of floc formation and increases floc size, reducing floc size variability and improving flocculation effectiveness.

[0017] Effect experiment (1) Preparation of simulated water samples. Kaolin, as a deflocculating substance, can remain suspended in fresh water for a long time and is difficult to settle. Therefore, it is often used as a model flocculation object in flocculation experiments. Dissolve 0.01 g of kaolin in 1000 g of water and mix well to prepare a kaolin solution with a mass fraction of 0.001% to simulate a turbid swimming pool water sample. The initial turbidity is 6.98 NTU.

[0018] (2) Flocculation experiment steps: A portable multi-parameter water quality analyzer was used to measure the turbidity index. Composite flocculants of different concentrations (0.01%, 0.03%, 0.1%, 0.2%, 0.5%) were added to 100 mL of kaolin water sample. The mixture was reacted at a speed of 800 r / min for 12 min. The stirring was stopped and the mixture was allowed to stand for 20 min. The turbidity of the supernatant was measured and the turbidity changes were recorded.

[0019] The results of the effect experiment show that ( Figure 3 The flocculation effect of different dosages was significantly different. The best flocculation effect was achieved when the dosage was 0.2%, and the turbidity removal rate of kaolin solution could reach 89%. The surface structure of the composite flocculant after the flocculation experiment was characterized, and the results were as follows: Figure 4 As shown in the figure, a large number of kaolin particle agglomerates are attached to the surface of the flocculant and in the cavities. The agglomerates formed by the flocculation reaction have a dense structure and a large coverage area, indicating that the flocculant has a good flocculation effect.

[0020] Performance comparison experiment Comparative experiment on the flocculation effect of different flocculants. Prepare 0.001% kaolin suspension to simulate water sample, test the turbidity of the original solution before the reaction, add 0.2% concentration of different types of flocculants to 100 mL kaolin water sample, including: 0# blank, no flocculant added; 1# chitosan flocculant (CS); 2# polyacrylamide flocculant (AM), 3# chitosan-polyacrylamide flocculant (CS-AM); 4# magnetic polysilicate aluminum zinc-chitosan-polyacrylamide composite flocculant (Fe3O4-PSAZn-CS-AM). Set the whole process to high speed (800r / min) for 12 min, stop stirring, let it stand for 20 min, take the supernatant to measure the turbidity, and record the turbidity change. The experimental results are as follows. Figure 5 Compared with the pure organic flocculant, the prepared Fe3O4-PSAZn-CS-AM organic / inorganic composite flocculant has the best flocculation effect and higher flocculation efficiency.

[0021] Actual use effect The prepared composite flocculant was used to treat the turbid swimming pool water sample obtained from a swimming pool in Zhengzhou. The initial water quality parameters were: turbidity = 1.08 NTU, COD concentration = 105.1 mg / L, urea concentration = 1.5 mg / L, UV 254 =0.046(cm -1 ).

[0022] Flocculation experiment steps: water samples were collected from the surface, middle water section and bottom of the swimming pool respectively. The collected water samples were mixed in a 1:1 ratio, and a flocculant with a concentration of 0.2% was added. The reaction was carried out at a speed of 800 r / min for 12 minutes. The stirring was stopped and the sample was allowed to stand for 20 minutes. The supernatant was taken to measure the turbidity, COD concentration, urea concentration and UV of the water sample. 254 .

[0023] Result analysis: Through the flocculation experiment on the collected turbid water samples, the effects of flocculants on the turbidity, COD concentration, urea concentration and UV 254 The removal rates were 89%, 92.4%, 87.7% and 91.6% respectively, indicating an ideal flocculation effect.

Claims

1. A method for preparing an organic / inorganic composite flocculant for swimming pool water treatment, characterized in that: The following steps are involved: S1. Preparation of magnetic nanoparticles: FeCl3·6H2O and FeCl2·4H2O were dissolved in 150 mL of 4% hydrochloric acid solution, iron powder was added to the FeCl2·4H2O solution and then mixed with the FeCl3·6H2O hydrochloric acid solution. While mixing, 25% ammonia water was added and stirred for 2 h. The mixture was allowed to stand and washed with deionized water and anhydrous ethanol for 3 times to obtain Fe3O4 magnetic nanoparticles with a particle size distribution of 8 to 20 nm. The particles were dried and ground at 50 °C for later use. The prepared Fe3O4 magnetic nanoparticle powder was dissolved in 50 mL of deionized water to prepare a concentration of 1.45 g·L -1 Fe3O4 magnetic nanoparticle solution; S2. Preparation of magnetic sodium silicate solution: at a concentration of 1.45 g·L -1 Sodium silicate powder was added to the Fe3O4 magnetic nanoparticle solution and 30% concentrated sulfuric acid and 0.1 mol·L -1 The pH value of the mixed solution was adjusted to 1.0 with sodium hydroxide, stirred in a water bath at 40°C for 2 h, and allowed to stand for 2 h to obtain a magnetic polysilicic acid solution. S3. Preparation of chitosan - polyacrylamide flocculant: chitosan and acrylamide were dissolved in glacial acetic acid solution, and ammonium cerium nitrate was used as an initiator to prepare chitosan - polyacrylamide flocculant CS-AM, and the prepared flocculant was stirred in glacial acetic acid solution for 24h for pretreatment; S4. Preparation of organic / inorganic composite flocculant: 0.427 mol·L of CS-AM were added to the magnetic polysilicic acid solution according to the ratio of n(Al+Zn) / n(Si) = 0.8, n(Al) / n(Zn) = 4, and m(Al+Zn) / m(CS-AM) = 4. -1 Al2(SO4)3·18H2O solution, 0.854 mol·L -1 The ZnSO4·7H2O solution and 0.5% pretreated CS-AM solution were cross-linked and stirred in a 40℃ water bath for 2 h, and then left to stand and mature for 24 h to obtain the Fe3O4-PSAZn-CS-AM composite flocculant.

2. The method for preparing the organic / inorganic composite flocculant for swimming pool water treatment according to claim 1, characterized in that: The composite flocculant is post-processed before use, and the post-processing includes first purifying with acetone, then washing with anhydrous ethanol until there are no impurities, and then drying in a constant temperature drying oven to a constant weight.

3. The composite flocculant prepared by the method for preparing an organic / inorganic composite flocculant for swimming pool water treatment as described in any one of claims 1-2 is used in swimming pool water treatment to adsorb heavy metal ions while adsorbing organic matter.

Citation Information

Patent Citations

  • Dephosphorization flocculating agent and preparation method thereof

    CN104261530A

  • Preparation method for polysilicate aluminum zinc and chitosan composite flocculant

    CN105110438A

  • Preparation method of magnetic composite flocculant and product thereof and application thereof

    CN108996647A

  • Preparation method of magnetic titanium aluminum polysilicate-sodium alginate composite flocculant

    CN113087098A

  • Polymer flocculents and preparation thereof

    EP1236748A1

Cited By

  • Temperature and pressure dual-function sensor, preparation method and application

    CN121230772A

  • Novel magnetic composite coagulant and application thereof

    CN121342191A

  • Organic-inorganic composite wastewater phosphorus removal agent and preparation method thereof

    CN121426255A